2015
DOI: 10.1111/cas.12832
|View full text |Cite
|
Sign up to set email alerts
|

Urinary laminin‐γ2 is a novel biomarker of non‐muscle invasive urothelial carcinoma

Abstract: Lack of appropriate biomarkers has hampered early detection of urothelial cancer (UC), therefore, development of biomarkers for its diagnosis at earlier stages is of importance. Laminin‐332 (Ln‐332, formerly Ln‐5), a component of basement membranes, consists of Ln‐α3, Ln‐β3, and Ln‐γ2 polypeptides. However, monomeric Ln‐γ2 alone is frequently expressed in malignant neoplasms. If Ln‐γ2 is also expressed in UC and secreted into the urine, its detection could be useful for UC diagnosis. Here, we evaluated Ln‐γ2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…Kamada et al . identified urinary laminin γ2 as a novel biomarker of nonmuscle invasive urothelial carcinoma; however, it was not determined whether laminin γ2 was present in urinary EVs …”
Section: Discussionmentioning
confidence: 99%
“…Kamada et al . identified urinary laminin γ2 as a novel biomarker of nonmuscle invasive urothelial carcinoma; however, it was not determined whether laminin γ2 was present in urinary EVs …”
Section: Discussionmentioning
confidence: 99%
“…The monomeric form of Ln‐γ 2 has been detected in various carcinomas (pancreas, stomach, tongue, oesophagus, colorectal, lung and cervix) . Recently, Ln‐γ 2 has been reported as a useful novel biomarker for some carcinomas (urothelial carcinoma, hepatocellular carcinoma) . Studies show that Ln‐γ 2 is overexpressed at the invasive front of a variety of carcinoma tissue as well as in highly invasive cancer cells, and that such cells secrete a large amount of cleaved forms of Ln‐γ 2 in conditioned medium .…”
Section: Discussionmentioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18)(19) Our preliminary results indicated that elevated serum monomeric Ln-c2 levels could be observed in patients with various malignancies, such as pancreatic adenocarcinoma (data not shown) and bladder carcinoma. (21) Although further analysis is required, serum monomeric Ln-c2 is a potentially useful biomarker for the screening of cancer in various organs, similar to the carcinoembryonic antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of monomeric Ln‐γ2 in the serum may be useful as a biomarker for HCC. In an earlier study, we developed a monoclonal antibody that preferentially recognizes the monomeric form of Ln‐γ2 and used it for ELISA to detect the Ln‐γ2 chain . We also developed a fully automated highly sensitive detection method for serum monomeric Ln‐γ2 based on a chemiluminescent immunoassay (CLIA).…”
mentioning
confidence: 99%
See 1 more Smart Citation